Analisis Parameter Pemotongan Terhadap Waktu Pemesinan pada Proses C-Axis Menggunakan Software CAM - Saputro, Rian Dwi Aji; Nur Muhammad Malikul ‘Adil; Muhamad Kamaludin; Yadi Hikmah Setiana; Agus Haris Abadi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
This study aims to analyze the effect of depth of cut and feed rate variations on machining time in the C-Axis collet process. The research method employed was an experimental approach using Mastercam software. This study's independent variables were variations in cut depth (0.5 mm, 0.8 mm, 1.0 mm) and feed rate (110 ft/min, 125 ft/min, 140 ft/min), while the controlled variable was a spindle speed of 1036 rpm. The tools used were 8 mm and 4 mm diameter flat endmills. The results showed that the shortest machining time was achieved in Toolpath 2 with a depth of cut of 1.0 mm and a feed rate of 140 ft/min, resulting in a time of 12.47 s. In contrast, the longest machining time occurred in Contour Toolpath 1 with a depth of cut of 0.5 mm and a feed rate of 110 ft/min, taking 141.15 s. This research can be further developed to establish standards for optimizing machining time efficiency in C-Axis processes.